2017
DOI: 10.3390/nu9080830
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Sodium and Potassium Excretion and Dietary Sources of Sodium in Maputo, Mozambique

Abstract: This study aimed to evaluate the urinary excretion of sodium and potassium, and to estimate the main food sources of sodium in Maputo dwellers. A cross-sectional evaluation of a sample of 100 hospital workers was conducted between October 2012 and May 2013. Sodium and potassium urinary excretion was assessed in a 24-h urine sample; creatinine excretion was used to exclude unlikely urine values. Food intake in the same period of urine collection was assessed using a 24-h dietary recall. The Food Processor Plus®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Specifically in Mozambique, although direct evidence of high sodium intake is scarce, a recent study based on 24-h urine samples of 100 Maputo dwellers showed mean urinary sodium excretion compatible with a daily intake twice the recommended by the WHO [11]. This is in line with the high prevalence of hypertension in Mozambique (two out of every five adults) [12].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Specifically in Mozambique, although direct evidence of high sodium intake is scarce, a recent study based on 24-h urine samples of 100 Maputo dwellers showed mean urinary sodium excretion compatible with a daily intake twice the recommended by the WHO [11]. This is in line with the high prevalence of hypertension in Mozambique (two out of every five adults) [12].…”
Section: Introductionmentioning
confidence: 71%
“…The WHO highly recommends [46] awareness raising, which has been shown a cost-effective [47] and essential step to change behaviors and reduce salt consumption at a population level [48], especially in developing countries, where addition of salt during food preparation or as seasoning on table were found to represent the main contributors to sodium intake [1,48]. In Mozambique, a recent investigation [11] found that discretionary sodium was the main source of salt consumption, corresponding to just over 60% of the total dietary sodium intake. In order to improve salt control actions, and, to reach the higher educated groups of the population, other strategies should also be adopted, probably by involving the government and industry, targeting processed foods [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies from six countries (Table 3) reported salt level in foods through food analysis 30,37,38,40,43,44 nutrition information panels, 52 and 24‐hour dietary recalls 39,53 . Salt levels in foods were high and variable, both within and between countries.…”
Section: Resultsmentioning
confidence: 99%
“…Almost 70.0% of men and 80.0% of women ingested less than the recommended 3510 mg/day of potassium. In a study carried out in the capital of another Portuguese-speaking country, Maputo, Mozambique, this percentage was 96.0% [ 52 ]. In South African adults, the non-compliance with the daily potassium recommendation was 91.0% [ 53 ].…”
Section: Discussionmentioning
confidence: 99%